Peningkatan Hasil Belajar Siswa Sekolah Dasar Pada Pelajaran Matematika Melalui Media Papan Berpaku: Indonesia - Zulhasni; Lestari Nuriah; Nursalim; Anggi Fitri; Ardi Yulis; Elsunarti (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2019)
This study aims to determine the improvement of student learning outcomes in mathematics through the media board. The formulation of the problem of this research is whether there is an increase in student learning outcomes in mathematics through nailed boards? This research is a Classroom Action Research (PTK). The object of this research is the use of nailed boards to improve learning outcomes in mathematics. The research was carried out in two cycles, each cycle consisting of two meetings, with stages, namely: planning / preparing for action, implementing the action, observing, and reflecting. Data collection techniques using observation techniques, learning outcomes tests, and documentation. Based on the research results, it is known that there is an increase in student learning outcomes before the action, Cycle I, and Cycle II. Before the action was taken, students only reached 50% or 8 students who had completed, and 8 students or 50% who had not. In the first cycle students who completed increased to 10 people or completeness only reached 62.5%. in cycle II, it turns out that the completeness of the students reached 13 students or with a percentage of 81.25%. Thus, the use of nailed board media can improve student learning outcomes in mathematics subjects.